Please Be Patient: A Cultural Phenomenological Study of Haemodialysis and Kidney Transplantation Care - Gunnarson, Martin (Socialmedicinsk tidskrift, 2016)
Artikeln är en sammanfattning av avhandlingen Please Be Patient: A Cultural Phenomenological Study of Haemodialysis and Kidney Transplantation Care.